VO #023 Proposal of extra works for audio visual and PA, IT system, security and access control of BRAC University new campus project - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding VO #023 proposal of extra works for audio visual and PA, IT system, security and access control of BRAC University new campus project.